4CPS-043 Drug-drug interactions with nirmatrelvir/ritonavir for COVID-19 and the role of hospital pharmacists. Issue 1 (23rd March 2023) - Miedes, J; Rodriguez, A; Barceló, J; Echeverría, D; Grau, S
Abstract : Background and Importance: Nirmatrelvir/ritonavir has recently been approved for treating COVID-19, but an elevated risk of drug-drug interactions (DDI) has been exposed. Aim and Objectives: The aim of this study was to evaluate DDI with nirmatrelvir/ritonavir and the role of hospital pharmacists. Material and Methods: Retrospective study in a tertiary hospital between May-September 2022. All patients that received nirmatrelvir/ritonavir were included. Data collected: demographic, age-adjusted Charlson comorbidity index, medical department, concomitant drugs. All DDI and pharmacy interventions were screened and categorised. Continuous data expressed as median (IQR). U-Mann Whitney for continuous variables and Chi-square for qualitative data. Results: A total of 48 patients with 350 concomitant drugs were selected. Female 24(50%), age 69(24-95) years, CHARLSON 5(0-12). DDI were detected in 26 (54.2%) patients and in 52 (14.9%) drugs. Seven (0-16) concomitant drugs per patient. Statistical significant differences were found with ATC and DDI category (p<0.001): cardiovascular system drugs had more X-category DDI (41.7%) and nervous system drugs had more C-category DDI (60.8%). Haematology department had more patients presenting any DDI (23.1%, p=0.047). No DDI provoked any adverse event during treatment with nirmatrelvir/ritonavir. Conclusion and Relevance: A high risk for DDI with nirmatrelvir/ritonavir was found, although most of them were mild and none provoked any adverse event. Cardiovascular system drugs showed the most severe DDI. Haematology patients and those receiving nervous system drugs had higher prevalence for DDI. Almost half of pharmacy recommendations were to discontinue the drug presenting the DDI. None of the pharmaceutical interventions induced any adverse event derived from the modification of concomitant treatment during nirmatrelvir/ritonavir administration. References and/or Acknowledgements: Conflict of Interest: No conflict of interest